Treatment of Intrabony Defect using Xenograft and Collagen membrane-A Case Report with Clinico-radiographic Evidence - Thapa, Victory; Shrestha, Sajeev; Adhikari, Khushbu; Bhandari, Suresh (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Periodontal regenerative procedures attempt to increase the periodontal attachment, bone level and reduce pocket depth in order to improve the immediate and long-term clinical results of periodontally compromised teeth. Guided Tissue Regeneration (GTR) membrane and bone graft materials or their combination has been used for reconstruction of periodontal apparatus. After reflecting a full-thickness flap, thorough debridement and root planing were accomplished in the present case. A bioabsorbable collagen membrane was placed over the xenograft filled defect to treat an intrabony defect. The one-year-follow up showed improvement in clinical parameters with radiographic evidence of bone fill.